Перспективні телевізійні системи, телебачення мережного протоколу - Вовченко, А. Р. (ХНУРЕ, 2025)
The evolution of television technologies has shifted towards network-based broadcasting, enabling higher flexibility, interactivity, and efficiency in content delivery. Modern IPTV and OTT (Over-the-Top) services utilize internet protocols to provide high-quality streaming with adaptive bitrate control, ensuring seamless viewing experiences. Advanced compression techniques such as HEVC (H.265) and AV1 optimize bandwidth usage while maintaining superior video quality. The integration of artificial intelligence enhances content recommendations and adaptive streaming. This study explores the future of television systems, focusing on network protocol-based broadcasting, AI-driven content management, and emerging transmission standards.
Keywords: телебачення мережного протоколу; evolution of television technologies